Implementasi Metode Balanced Scorecard dalam Perancangan Sistem Penilaian Kinerja Perguruan Tinggi Vokasi - Imam Bayhaqi (Universitas Batanghari Jambi, 2020)
The Balanced Scorecard (BSC) is one tool that can be used to measure the performance of an organization. To improve the quality of education, a performance appraisal system is needed to measure the ability of universities to carry out their functions. In this study, the authors will design a performance appraisal system for vokasi colleges by integrating indicators in BAN-PT, AUN-QA, MQA, and TEQSA. Integrating indicators aims to enable vokasi colleges to compete nationally and internationally. The results of this study obtained 90 indicators divided into four BSC perspectives. Each value will be calculated with the Analytic Hierarchy Process (AHP) method. The performance appraisal system that has been designed will be used by vokasi colleges to measure its performance so that it can be seen that improvements will be made by vokasi colleges to compete at national and international levels.